The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1677/joe-08-0206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aglycone genistein in a rat experimental model of postmenopausal metabolic syndrome

Abstract: Genistein aglycone, a soy derived isoflavone, has been demonstrated to be effective in reducing cardiovascular risk in postmenopausal women. We therefore investigated its effects in an experimental model of postmenopausal metabolic syndrome. Female spontaneously hypertensive obese rats (SHROB, nZ40), a genetic model of syndrome X, and age-matched Wistar Kyoto (WKY, nZ40) rats were used. A group of SHROB (nZ20) and WKY (nZ20) animals were ovariectomized (OVX). Four weeks after surgery all animals were randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 40 publications
4
33
0
5
Order By: Relevance
“…In addition, the effect of OVX on serum TAG levels is also controversial. Some studies have reported a reduction in serum TAG levels after OVX (Barsalani et al 2008;Paquette et al 2007b), while others have not observed any changes (Bitto et al 2009;Sanchez-Mateos et al 2007;Meli et al 2004). These contradictory results could be due to factors such as the diet, the subject's metabolic conditions and the duration of the study.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the effect of OVX on serum TAG levels is also controversial. Some studies have reported a reduction in serum TAG levels after OVX (Barsalani et al 2008;Paquette et al 2007b), while others have not observed any changes (Bitto et al 2009;Sanchez-Mateos et al 2007;Meli et al 2004). These contradictory results could be due to factors such as the diet, the subject's metabolic conditions and the duration of the study.…”
Section: Discussionmentioning
confidence: 98%
“…One major limitation in this direction appears to be its high MED 100 in rats. Pharmacological studies, however, demonstrate that MED of a drug in humans is almost 1/7th of that in rats (Bitto et al 2009). It is also important to note that the bioavailability of puerarin in vivo is often limited by its insolubility.…”
Section: Discussionmentioning
confidence: 99%
“…콩은 수 천년 동안 여러 아시아 지역에서 단백질의 중요한 급원 식품 으로 공급되어 왔고 [9,28,40] 또한 대두 단백질과 더불어 콩에 다량 함유된 isoflavone은 폐경기 증상을 완화시키고, 심혈관 질환, 골다공증 및 암의 위험을 감소시킨다는 연구들이 많이 보고되었다 [6,17,26].…”
Section: 서 론unclassified